Broiler Surface Temperature and Behavioral Response under Two Different Light Sources - Araújo,FE (2015)
Light is an important environmental variable for the regulation and control of broiler behavior. Some light sources may also add heat to the rearing environment, and indirectly affect the heat exchange between the birds and the environment. This study aimed at investigation the surface temperature and behavioral response of broilers reared in an environment with monochromatic light emitted diode (LED). Broilers were reared inside commercial dark houses under two treatments: fluorescent or LED light sources. Bird surface temperature and behavior was monitoredfrom the first day of grow-out. The houses were virtually divided in four quadrants, and the variables were monitored in the geometric center of each quadrant. Surface temperature results were mapped, behavioral responses were divided as normal and abnormal, and their interaction with light source was tested. Broiler surface temperature in both houses presented lack of homogeneity, independently of the light source. No effect of the light source on any of the evaluated behavior was found in the present study. The long life and energy savings obtained with the LED light source suggest its use in broiler production.